Reading with the eyes and under the skin: Comprehending conflicting digital texts. (21st November 2019) - Mason, Lucia; Zaccoletti, Sonia; Scrimin, Sara; Tornatora, Maria Caterina; Florit, Elena; Goetz, Thomas
Abstract: This study investigated the contribution of both physiological and behavioural process data to the comprehension of conflicting digital texts. We measured skin conductance level (SCL) as an index of arousal and the first‐pass and look‐back fixation times as indices of visual behaviour while reading. Forty‐eight seventh graders read four webpages on genetically modified food, and their comprehension of the texts was measured using a short essay. Results showed that the type of webpage did not differentiate the process data. Statistical procedures for the comparison of a series of regression models revealed that SCL and first‐pass fixation time negatively predicted multiple‐text comprehension while also considering the control variables. The more the students were aroused while reading and the longer the processing time during the first encounter with the reading material, the poorer their comprehension of the conflicting texts. However, the interaction of prior knowledge and arousal positively predicted multiple‐text comprehension. A slope analysis revealed that when participants had high prior knowledge and high arousal during reading, their postreading comprehension performance increased. Lay Description: What is already known about this topic Multiple‐text comprehension requires readers to construct both an intertext model and an integrated mental model. The process of reading various texts on the same topic can be traced by physiological and behavioural data. Skin conductance level is an index of physiological arousal. First‐ and second‐pass fixation time are indices of visual behaviour during the immediate and delayed text processing. What this paper adds Physiological arousal per se is negatively associated with the comprehension of various digital texts on the debated topic of genetically modified food. The duration of the first pass is negatively associated with multiple‐text comprehension. The interaction of prior topic knowledge and physiological arousal is positively associated with multiple‐text comprehension. When pre‐existing knowledge is high, multiple‐text comprehension is greater with high arousal. Implications for practice and/or policy Recall of prior knowledge before reading is a beneficial starting point for comprehension processes. Physiological arousal in combination with prior knowledge can reflect interest and enjoyment during reading or less processing effort for comprehension within and across texts. Videos with students' gaze replays can be used to solicit their reflections on the processing behaviour they activated while reading digital texts on the same content, and what processing behaviour is more conducive to successful multiple‐text comprehension.